Understanding Capacity and Optimizing Meaningful Engagement among Persons Living with Dementia. (May 2023) - Kemp, Candace L; Bender, Alexis A; Morgan, Jennifer Craft; Burgess, Elisabeth O; Epps, Fayron R; Hill, Andrea Michelle; Perkins, Molly M
Meaningful engagement is a key dimension of quality of life among persons living with dementia, yet little is known about how to best to promote it. Guided by grounded theory methods, we present analysis of data collected over a 1-year period in four diverse assisted living (AL) communities as part of the study, "Meaningful Engagement and Quality of Life among Assisted Living Residents with Dementia." Our aims are to: (a) learn how meaningful engagement is negotiated among AL residents with dementia and their care partners; and (b) identify how to create these positive encounters. Researchers followed 33 residents and 100 care partners (formal and informal) and used participant observation, resident record review, and semi-structured interviews. Data analysis identified "engagement capacity" as central to the negotiation of meaningful engagement. We conclude that understanding and optimizing the engagement capacities of residents, care partners, care convoys, and settings, are essential to creating and enhancing meaningful engagement among persons living with dementia.